Relationship Between Patient Satisfaction and Pharmaceutical Services at Scholoo Keyen Regional Hospital 2024 - Ferida Battiling; Nilawati Uly; Achmad R. Muttaqien Al-Maidin; Zamli (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The quality of hospital pharmaceutical services must be maintained because it greatly influences patient satisfaction. Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the patient's quality of life. Patients will receive satisfaction from the quality of service provided by the hospital. Objective: The aim is to ascertain the correlation between the level of outpatient satisfaction and the quality of pharmaceutical services at the outpatient depot pharmacy installation at Scholoo Keyen Regional Hospital, South Sorong Regency, in 2024. Method: We conducted quantitative descriptive analytical research using a given questionnaire, and then we conducted interviews to supplement the qualitative data, deepening the field's findings and producing a comprehensive understanding of the studied phenomenon. Result: The satisfaction variable yielded the following results: 1 person (4%) expressed dissatisfaction, 91 expressed satisfaction (37%), and 154 expressed extreme satisfaction (62.6%). According to the reliability dimension, service quality was not important in category 0 (0%), important in category 11 (4.5%), and very important in category 235 (95.5%). Responsiveness: not important 0 (0%), important 9 people (3.7%), and very important 237 (96.3%). Assurance: not important 0 (0%), important 7 (2.8%), and very important 239 (97.2%). Empathy is not important at 0 (0%), important at 8 (3.3%), and very important at 238 (96.7%). Empathy is classified as tangible, not important at 0%, important at 20 (8.1%), and very important at 226 (91.9%). The Kruskall-Wallis test found that patients were satisfied with the services they received on all five dimensions: reliability (0.014), responsiveness (0.000), assurance (0.008), empathy (0.003), and tangible (0.009). Conclusion: According to the Kruskal-Wallis test, the p-value for satisfaction with employee performance was 0.000. p-valued 0,000 < 0,05 until Ho rejected If accepted, we can assert a relationship between employee satisfaction and performance in the RSUD Scholoo Keyen district of Sorong South.